Development of Tense and Aspect Systems - Gvozdanović, Jadranka (Benjamins current topics ;, 2022)
Linguistic construal of time lies at the center of language and language use; it is also one of the cognitive foundations of culture. The focus of the papers in this volume is on historical developments of genetically different aspect and tense systems across continents.